Development of Online Promotion to Increase the Marketing Attractiveness of Batik Products - Eva Yuniarti Utami; Audita Nuvriasari (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose This community service program aims to increase sales of WOU Batik through optimizing online marketing. Besides that, it is aimed at increasing the skills and knowledge of resellers in compiling and utilizing marketing calendars as a promotion support tool. Methods - The method used in this community service activity is through the transfer of knowledge and technology which is manifested in reseller training activities and preparation of marketing guidelines in the form of a marketing calendar. At the end of the activity, program evaluation and monitoring programs are carried out. Result and discussions - The result of this community service activity is an increase in partners' knowledge and skills in compiling and utilizing marketing calendars so that promotional materials become more attractive. It is hoped that this interesting marketing communication can improve marketing performance. Conclusion - Resellers play an important role in distributing products from producers to consumers. For this reason, companies need to properly manage relationships with resellers, one of which is through training and mentoring activities to package promotions attractively and complete promotional tools so that it is hoped that they can provide profitable benefits for both parties.